Lectures on Lyapunov exponents - Viana, Marcelo (Cambridge : Cambridge University Press, 2014)
The theory of Lyapunov exponents originated over a century ago in the study of the stability of solutions of differential equations. Written by one of the subject's leading authorities, this book is both an account of the classical theory, from a modern view, and an introduction to the significant developments relating the subject to dynamical systems, ergodic theory, mathematical physics and probability. It is based on the author's own graduate course and is reasonably self-contained with an extensive set of exercises provided at the end of each chapter. This book makes a welcome addition to the literature, serving as a graduate text and a valuable reference for researchers in the field.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Lyapunov exponents